2018
DOI: 10.1186/s12886-018-0945-5
|View full text |Cite
|
Sign up to set email alerts
|

Association between genetic variation of complement C3 and the susceptibility to advanced age-related macular degeneration: a meta-analysis

Abstract: BackgroundThe purpose of this study is to discuss whether genetic variants (rs2230199, rs1047286, rs2230205, and rs2250656) in the C3 gene account for a significant risk of advanced AMD.MethodsWe performed a meta-analysis using electronic databases to search relevant articles. A total of 40 case-control studies from 38 available articles (20,673 cases and 20,025 controls) were included in our study.ResultsIn our meta-analysis, the pooled results showed that the carriage of G allele for rs2230199 and the T alle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 60 publications
3
16
0
Order By: Relevance
“…The highest score of association was CFH (0.999), Harrison et al suggested the decreased heparin-binding affinity caused by the Y402H polymorphism (a common SNP in CFH gene) may recognize of SCR7 H402 , which may contribute to the pathogenesis of AMD [54]. C3 gene contains many SNPs, our previous meta and Zhang et al both detected some increased and decreased SNPs in AMD [19,55]. Wang et al performed a systematic analysis and suggested rs641153 in the CFB gene was a protective factor in advanced AMD both in Caucasians and Asians [17].…”
Section: Discussionmentioning
confidence: 70%
“…The highest score of association was CFH (0.999), Harrison et al suggested the decreased heparin-binding affinity caused by the Y402H polymorphism (a common SNP in CFH gene) may recognize of SCR7 H402 , which may contribute to the pathogenesis of AMD [54]. C3 gene contains many SNPs, our previous meta and Zhang et al both detected some increased and decreased SNPs in AMD [19,55]. Wang et al performed a systematic analysis and suggested rs641153 in the CFB gene was a protective factor in advanced AMD both in Caucasians and Asians [17].…”
Section: Discussionmentioning
confidence: 70%
“…We found a variant of ADAMTS13 (rs2301612, missense) in 49 (51%) of patients, previously described in congenital TTP [ 42 ]. We also detected two missense risk factor variants, previously described in complement-related diseases: rs2230199 in C3 (21 patients) [ 43 ]; and rs800292 in CFH (34 patients) [ 44 ]. Among them, 31 (32%) patients had a combination of these characterized variants (18 in the discovery and 13 in the validation cohort).…”
Section: Resultsmentioning
confidence: 95%
“…C3 is the most abundant complement component, is involved in all three complement cascade pathways and certain single nucleotide polymorphisms are associated with higher risk of developing AMD [22,23,[50][51][52][53][54][55][56][57][58][59]. Furthermore, elevated plasma levels of C3 have been reported in AMD patients [27,28,60,61].…”
Section: Discussionmentioning
confidence: 99%